Meningkatkan Kompetensi Teknologi Informasi Komunikasi Melalui In House Training (IHT) Pada Guru UPTD SMP Negeri 9 Metro Tahun Pelajaran 2020/ 2021 - Agus Susetyo (Peneliti.net, 2022)
The purpose of this reseach was to find out that the implementation of In House Training can improve the competence of Information and Communication Technology for teachers at UPTD SMP Negeri 9 Metro. ICT is a supporter of teachers in learning, the low competence of the mastery of ICT is one of the obstacles in the implementation of learning which if not overcome will result in low student learning outcomes in general. At UPTD SMP Negeri 9 Metro, the mastery of ICT by teachers has not been maximized. The teacher's ability to master ICT is low. It can be seen from the initial data collection that only 15 of the 49 teachers who master or are proficient in mastering ICT. The implementation of In House Training (IHT) activities can improve the ability of teachers in mastering ICT. The results of data analysis show that the teacher's activity in In House Training (IHT) activities achieved in the first cycle is an average of 71%, in the second cycle is 81.2 % and 95.1% in cycle III, while the ability to master Technology and Communication (ICT) mastered by teachers in cycle I was 63.35%, in cycle II was 72.6% and in cycle III 95.1%. It can be seen that the implementation of In House Training (IHT) activities has a positive influence on increasing the ability to master Information and Communication Technology (ICT) for teachers at UPTD SMP Negeri 9 Metro